Rapid risk assessment to address emerging concerns of HPAI in raw and pasteurized milk - Yuhuan Chen; Kara J. Dean; Gavin J. Fenske; Sarah I. Murphy; Alexandra Gavelek; Régis Pouillot; Jane M. Van Doren; Sherri Dennis (PLoS ONE, 2025)
An outbreak of highly pathogenic avian influenza A, subtype H5N1, first reported in U.S. dairy cattle in March 2024, raised concerns of an emerging food safety threat from the virus in the milk supply. To support potential regulatory responses, we conducted a rapid assessment of the predicted risk to U.S. consumers of cow’s milk with two complementary and parallel approaches: a “bottom-up” quantitative risk assessment model that integrated data on virus levels in milk, milk consumption, and dose response; and a “top-down” epidemiological analysis that linked current novel flu illness detection to the consumption of raw and pasteurized milk. The dynamic use of the approaches accommodated rapidly evolving data in a range of risk scenarios. The risk assessment model identified pasteurization as a critical control for H5N1 in milk and highlighted the need for i) the targeted sampling of bulk tank raw milk in affected states pre-pasteurization, ii) raw milk herd surveillance and sampling, and iii) a better understanding of ingestion as a route of H5N1 infections for humans. This novel approach and the findings from this study promoted informed decision-making in an evolving outbreak investigation. This methodology can be leveraged in the conduct of future risk assessments to address emerging pathogen outbreaks that impact the food supply.